Prevalence, clinical correlates, and outcomes of anaemia in multi‐ethnic Asian patients with heart failure with reduced ejection fraction. (31st March 2018) - Goh, Vera J.; Tromp, Jasper; Teng, Tiew‐Hwa K.; Tay, Wan Ting; Van Der Meer, Peter; Ling, Lieng Hsi; Siswanto, Bambang B.; Hung, Chung‐Lieh; Shimizu, Wataru; Zhang, Shu; Narasimhan, Calambur; Yu, Cheuk Man; et al.
Abstract: Aims: Recent international heart failure (HF) guidelines recognize anaemia as an important comorbidity contributing to poor outcomes in HF, based on data mainly from Western populations. We sought to determine the prevalence, clinical correlates, and prognostic impact of anaemia in patients with HF with reduced ejection fraction across Asia. Methods and results: We prospectively studied 3886 Asian patients (60 ± 13 years, 21% women) with HF (ejection fraction ≤40%) from 11 regions in the Asian Sudden Cardiac Death in Heart Failure study. Anaemia was defined as haemoglobin <13 g/dL (men) and <12 g/dL (women). Ethnic groups included Chinese (33.0%), Indian (26.2%), Malay (15.1%), Japanese/Korean (20.2%), and others (5.6%). Overall, anaemia was present in 41%, with a wide range across ethnicities (33–54%). Indian ethnicity, older age, diabetes, and chronic kidney disease were independently associated with higher odds of anaemia (all P < 0.001). Ethnicity modified the association of chronic kidney disease with anaemia ( P interaction = 0.045), with the highest adjusted odds among Japanese/Koreans [2.86; 95% confidence interval (CI) 1.96–4.20]. Anaemic patients had lower Kansas City Cardiomyopathy Questionnaire scores ( P < 0.001) and higher risk of all‐cause mortality and HF hospitalization at 1 year (hazard ratio = 1.28, 95% CI 1.08–1.50) compared with non‐anaemic patients. The prognostic impact of anaemia was modified by ethnicity ( P interaction = 0.02), with the greatest hazard ratio in Japanese/Koreans (1.82; 95% CI 1.14–2.91). Conclusions: Anaemia is present in a third to more than half of Asian patients with HF and adversely impacts quality of life and survival. Ethnic differences exist wherein prevalence is highest among Indians, and survival is most severely impacted by anaemia in Japanese/Koreans.